Innovating Tahfidz Learning in the Covid-19 Pandemic: a Case Study in Indonesia - Nadhifah, Nadhifah; Mustaqim, Abdul; Syukur, Fatah; Mustofa, Mahmud Yunus; Azizah, Nurul (Universitas Negeri Semarang, 2023)
The COVID-19 pandemic has caused problems in learning tahfidz Al-Qur'an in Indonesia. One of the issues is how to keep the accuracy of reading the Qur'an related to lip movements and makharij letters which should be held through talaqqi (face-to-face) method but now it is conducted in virtual learning. This paper aims to analyze the innovation of tahfidz Al-Qur'an learning in Indonesia during the COVID-19 pandemic. This research uses qualitative data taken from observations and in-depth interviews. The research involves students, educators, and school principals. The data are analyzed using the triangulation technique based on a phenomenological mindset. The results show that (1) the learning of Al-Qur'an tahfidz during the pandemic is conducted online using supporting media technology that can accommodate, integrate, and unify the management of Al-Qur'an tahfidz learning; (2) Al-Qur'an tahfidz learning innovation can solve the existing problems by paying attention more to lip and tongue movements and sounds that the students produce, and; (3) Al-Qur'an tahfidz learning innovation has positive implications for the student's knowledge and skill competencies with satisfactory results. Their good outcomes may also be much better with the improvement of their attitudes in learning. This research suggests further research by developing a virtual tahfidz learning method to provide other alternatives to the tahfidz learning method during the COVID-19 pandemic.